CHROMOSOME NUMBERS OF THE EDELWEISS, LEONTOPODIUM (ASTERACEAE, COMPOSITAE – GNAPHALIEAE). (24th February 2014) - Stille, J. S.; Jaeger, M.; Dickoré, W. B.; Ehlers, K.; Holzhauer, S. I. J.; Mayland-Quellhorst, E.; Safer, S.; Schwaiger, S.; Stuessy, T. F.; Stuppner, H.; Wissemann, V.
<x content-type="archive" xml:space="preserve">Abstract</x> The genus Leontopodium (Pers.) R.Br. (Asteraceae, Compositae) is economically important for both pharmaceutical and horticultural purposes. This importance, however, has not led to a good understanding of species coherence and the delimitation of species. One fundamental aspect of a good understanding of a species is how many chromosomes it has and any possible indication of polyploidy. Here we present somatic chromosome numbers for 16 Leontopodium species, of which six are new for science. The results indicate basic chromosome numbers of x = 6, 8, 9 and 11, with x = 8 being most frequent among the species examined. While obviously including several distantly related lineages, the x = 8 species have distributions that are concentrated in the centre of diversity of the genus in southwest China. We identified two 'species-pairs' (Leontopodium dedekensii–L. sinense and L. souliei–L. calocephalum) in which the tetraploid species has more vigorous growth, but is confined geographically to the centre of diversity. The diploid species ascend to generally higher elevations and extend more towards the Tibetan Plateau. In contrast, our data also suggest range expansions in other polyploid species, such as the hexaploid Leontopodium ochroleucum extending into the mountains of Central Asia. Deviations from x = 8 are found at the edges of the wide Eurasian distribution of the genus. These may relate to subsequent range expansions into the Himalayas, northern Asia, the Far East, and a far disjunctive expansion to the mountains of Europe. This implies an increased ability of these species to colonise mountain floras and adapt to different environmental conditions. Thus, formation of higher ploidy levels in general might be significant for a successful radiation process.